Dietary intervention with avocado (Persea americana Mill.) ameliorates intestinal inflammation induced by TNBS in rats - de Oliveira, Ellen Cristina Souza [UNESP]; Dalmau, Lesvi Moya [UNESP]; de Almeida Costa, Celso Acácio Rodrigues [UNESP]; de Almeida Junior, Luiz Domingues [UNESP]; Ballard, Cíntia Reis; Maróstica Junior, Mário Roberto; Stahl, Marcella Aparecida; Grimaldi, Renato; Witaicenis, Aline [UNESP]; Di Stasi, Luiz Claudio [UNESP] (Springer Nature, 2023)
Nutritional interventions have been shown to be an interesting approach for the treatment of chronic diseases, including inflammatory bowel disease (IBD). Persea americana Mill. (avocado), is a potential food to be used for the prevention or treatment of intestinal inflammation, due to its nutritional value and pharmacological effects. In this study we evaluated if the dietary intervention with avocado fruit pulp could as an intestinal anti-inflammatory diet using a trinitrobenzenesulfonic acid (TNBS) model of intestinal inflammation in rats. For this purpose, 5, 10 or 20% of avocado fruit pulp was incorporated in the diet of rats, for 21 days before and 7 days after TNBS-induced intestinal inflammation. Dietary intervention with avocado fruit pulp (20%) decreased the extension of colonic lesions (1.38 ± 0.99 vs. 2.67 ± 0.76 cm), weight/length colon ratio (151.03 ± 31.45 vs. 197.39 ± 49.48 cm), inhibited myeloperoxidase activity (891.2 ± 243.2 vs 1603 ± 158.2 U/g), reduced tumor necrosis factor-α (53.94 ± 6.45 vs. 114.9 ± 6.21 pg/mg), interleukin-1β (583.6 ± 106.2 vs. 1259 ± 81.68 pg/mg) and interferon gamma (27.95 ± 2.97 vs. 47.79 ± 3.51 pg/mg) levels and prevented colonic glutathione depletion (2585 ± 77.2 vs 1778 ± 167.2 nmol/g). The consumption of enriched diet with 20% avocado pulp by 28 days did not promote any alterations in the biochemical or behavioral parameters evaluated. Avocado showed intestinal anti-inflammatory activity, modulating immune response, and acting as antioxidant. The dietary intervention with avocado was safe, suggesting its potential as a complementary treatment in intestinal inflammation.
Keywords: Avocado pulp, anti-inflammatory activity; Dietary intervention; Inflammatory bowel disease; Persea americana Mill